2009
DOI: 10.1111/j.1365-3148.2009.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Is dengue a threat to the blood supply?

Abstract: Dengue is the most common arthropod-borne infection worldwide, affecting at least 50 million people every year and endemic in more than 100 countries. The dengue virus is a single-stranded RNA virus with four major serotypes. Infection with one serotype confers homotypic immunity but not heterologous immunity, and secondary infection with another serotype may lead to more severe disease. The major route of transmission occurs through the Aedes aegypti mosquito vector, but dengue has also been transmitted throu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
79
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 48 publications
(66 reference statements)
1
79
0
1
Order By: Relevance
“…Blood transfusion for dengue is only indicated for patients with significant clinical bleeding. 5 In our two patients, there was no evidence of hemorrhage or decrease in hemoglobin levels, and one of these patients showed an increase in hematocrit 20% from baseline. These patients do not meet the criteria for blood transfusions and represent over-treatment by physicians.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Blood transfusion for dengue is only indicated for patients with significant clinical bleeding. 5 In our two patients, there was no evidence of hemorrhage or decrease in hemoglobin levels, and one of these patients showed an increase in hematocrit 20% from baseline. These patients do not meet the criteria for blood transfusions and represent over-treatment by physicians.…”
Section: Discussionmentioning
confidence: 97%
“…This vector is highly susceptible to the dengue virus and feeds preferentially on human blood. 4 These mosquitoes are daytime feeders and have crepuscular 5 and nocturnal habits, 6 which further enhance dengue transmission. These nocturnal components expand their feeding duration to periods when persons are at home at night.…”
Section: Introductionmentioning
confidence: 99%
“…There is no significant increase in bleeding in patients who have co-morbidities (p=0.447). A previous study done on adult patients with dengue fever and DHF showed that age above 65 years, history of dengue infection, diabetes mellitus, hypertension and renal insufficiency have been identified as being significantly associated with DHF/DSS 10 . The aforementioned study mentioned that the presence of co-morbidities will increase the risk to develop DHF, but not necessarily bleeding.…”
Section: Discussionmentioning
confidence: 99%
“…Although viremia in vertebrate hosts has been estimated for dengue between 10 5 and 10 9 RNA copies/mL [30], there are reports of situations with low plasma viremia during early stages of infection, for example, reinfection by DENV-3 with high levels of preexisting neutralizing antibodies [31,32], epidemics with endemic DENV-3 strains associated with low viremia in humans [30], primary infections with a duration of less than five days [33], newborn infected with DENV-2 through a contagious via associated with transfusion [34], and even infections of two genotypes of DENV-2 in a humanized mouse model [35].…”
Section: Discussiónmentioning
confidence: 99%